Typescript list of members of the Ballycrovane Company, Rossmacowen Company, Ardea Company (Co. Kerry) and the Ardgroom Company, 5th Battalion, 5th Cork Brigade, Irish Republican Army, - Irish Republican Army (1916)
List distinguishes between those who were neutral during the Civil War, those who joined the Free State Army or the Gardai, those who were interned, those who remained active (on the Anti-Treaty side), and those who have died. Also with details of their addresses when they joined up and their current addresses (probably late 1930's), showing that a high proportion emigrated to England, Canada or the United States of America.